Survey of Xylosandrus compactus (Coleoptera: Curculionidae) Attack Levels in Malang: Influence of Land Management and Habitat Conditions - Manurung, Jihan Salmaa Afiifah; Rahardjo, Bambang Tri; Syamsulhadi, Mochammad; Muhammad, Faiz Nashiruddin (AGRIVITA Journal of Agricultural Science, 2025)
Humidity at a low level reduces the growth and development of borer pests. On the contrary, coffee plants under shaded conditions grow and develop under higher humidity and lower temperatures, causing the risk of X. compactus. This research aimed to evaluate differences in twig borer attack intensity and their relationship with environmental and management factors. From August to December 2023, research was done in twelve coffee plantations in UB Forest, Dampit, Bangelan, and Ngantang. Direct observations such as infestation intensity, temperature, relative humidity, canopy cover, and the diversity and abundance of weeds and shade trees, were done. We also recorded the pruning, pesticide use, and fertilizer application. The relationships between infestation intensity and habitat management variables were analyzed using general linear models. We concluded that the twig borer infestation intensity varied widely among plantations, with the highest levels recorded in Ngantang. Temperature, canopy cover, species diversity, and weed abundance did not significantly influence infestation levels. Nevertheless, relative humidity presented a significant positive correlation with infestation intensity. Moreover, among the observed management practices, only pruning intensity significantly reduced twig borer infestation, while pesticide application and fertilization had no significant effect.